Knowledge Attitude and Exercise Behavior in Relation to Exercise Readiness of Students in College of Integrated Science and Technology, Rajamangala University of Technology Lanna - Jaimuang, Sirinapa (Princess of Naradhiwas University Journal, 2022)
This study aimed to examine knowledge, attitude, and exercise behavior in relation to exercise readiness of College of Integrated Science and Technology (CISAT) students, Rajamangala University of Technology Lanna (RMUTL). The population of this study were 28 freshmen from Mechatronics Engineering program, year of 2020. The data were collected using knowledge, attitude and physical activity behavior needs questionnaires. Data were analyzed using descriptive statistics and Pearson Product- Moment Correlation Coefficient. The results showed that the population had a good level of knowledge in exercise (µ = 4.08, σ =0.93), exercise behavior (µ = 3.77, σ = 1.03), exercise readiness (µ = 3.71, σ = 1.03) and a moderate level in exercise attitude (µ = 3.31, σ = 1.37). The findings showed that exercise behavior (r = .644**, p = .000), attitude (r = .512**, p = .005) and knowledge (r = .495**, p = .007) were related to the students’ exercise readiness with statistical significance at .05, a moderate correlation. The relationship between the personal data of variables; gender, age, exercise time and exercise method and reasons for exercising and not exercising were not statistically significant with exercise readiness. The physical activity risk assessment (r = .685**, p = .000) was related to the students’ exercise readiness with statistical significance at .05, a moderate correlation.